Tuturan Ritual Hambor Haju pada Masyarakat Manggarai Sebuah Kajian Linguistik Kebudayaan - Raru, Gregorius (Paradigma: Jurnal Kajian Budaya, 2016)
This study explores the cultural imagery in “ritual speech Hambor Haju at Manggaraian society: a cultural linguistic study”, with two problems that should be researched. Those problems are (1) verbal symbols in ritual speech Hambor Haju; (2) imagery in ritual speech Hambor Haju. This qualitative research was carried oiut in Maggarai Regency, Flores, East Nusa Tenggara province. The data were obtained through observation, interview, documentation study, listening, recording, and note taking. The result of the data analysis is informally reported and verbally described. The data were analyzed using a number of theories and paradigms, particularly cultural linguistics theory from Gary B. Palmer. The results of the study indicates that (1) esthetic form of ritual speech Hambor Haju consists of parallelism and metaphor; (2) verbal symbols of ritual speech Hambor Haju includes grammatical aspects, literary style, and discourse scenario; (3) imagery in ritual speech Hambor Haju consists of (a) esthetics imagery; (b) unity/togetherness imagery; (c) respecting imagery; (d) deliberations imagery; (e) sacred imagery; (f) act imagery; (g) loyalty imagery; (h) ideology imagery; (i) emancipation imagery; (j) seriousness imagery; and (k) pro-existence imagery.